2012
DOI: 10.3390/ma5091661
|View full text |Cite
|
Sign up to set email alerts
|

Natural Melanogenesis Inhibitors Acting Through the Down-Regulation of Tyrosinase Activity

Abstract: Melanogenesis is a biosynthetic pathway for the formation of the pigment melanin in human skin. A key enzyme, tyrosinase, catalyzes the first and only rate-limiting steps in melanogenesis, and the down-regulation of enzyme activity is the most reported method for the inhibition of melanogenesis. Because of the cosmetically important issue of hyperpigmentation, there is a big demand for melanogenesis inhibitors. This encourages researchers to seek potent melanogenesis inhibitors for cosmetic uses. This article … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
168
1
8

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 214 publications
(204 citation statements)
references
References 98 publications
(107 reference statements)
3
168
1
8
Order By: Relevance
“…Surprisingly, DNM affected neither the enzyme activity ( Figure 3A) nor the intracellular tyrosinase protein level ( Figure 3B and 3C). Most melanogenesis inhibitors discovered thus far inhibit melanogenesis through down-regulation of intracellular tyrosinase activity [2]. However, our results suggest that DNM exhibited antimelanogenesis activity probably via a different mechanism.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…Surprisingly, DNM affected neither the enzyme activity ( Figure 3A) nor the intracellular tyrosinase protein level ( Figure 3B and 3C). Most melanogenesis inhibitors discovered thus far inhibit melanogenesis through down-regulation of intracellular tyrosinase activity [2]. However, our results suggest that DNM exhibited antimelanogenesis activity probably via a different mechanism.…”
Section: Discussioncontrasting
confidence: 52%
“…Although melanin primarily serves a photoprotective function, over-production and accumulation of melanin result in several skin disorders including freckles, melasma, age spots, and other hyper-pigmentation syndromes. Thus several studies on the treatment of skin disorders have focused on inhibiting melanogenesis and preventing abnormal pigmentation [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Pigmentary changes due to the accumulation of melanin are another major characteristic of photoaging. Tyrosinase is a key enzyme that catalyzes melanin biosynthesis in melanocytes (4,6). Previous studies have identified a significant association between the activities of topical treatments, including anti-aging, skin , HUI-YUN WANG 3 , JAI-SING YANG 6 and FU-AN CHEN evening, and anti-wrinkling, and decreased elastase and tyrosinase activity (4,5,7).…”
Section: Introductionmentioning
confidence: 99%
“…Tyrosinase is a key enzyme that catalyzes melanin biosynthesis in melanocytes (4,6). Previous studies have identified a significant association between the activities of topical treatments, including anti-aging, skin , HUI-YUN WANG 3 , JAI-SING YANG 6 and FU-AN CHEN evening, and anti-wrinkling, and decreased elastase and tyrosinase activity (4,5,7). Burdock (Arctium lappa L.), a biennial plant belonging to the Compositae family, has been cultivated in Eastern Asian countries, particularly in Taiwan, China and Japan for use in cooking and in folk medicine as a diuretic, antipyretic and blood purifying agent (8-10).…”
Section: Introductionmentioning
confidence: 99%
“…There are three known mechanisms for the down-regulation of the tyrosinase activity 18 . The most common mechanism reported is the direct inhibition of tyrosinase catalytic activity through tyrosinase inhibitors.…”
Section: Resultsmentioning
confidence: 99%